PEMBERIAN KREDIT DENGAN JAMINAN TANAH SURAT KETERANGAN (SK) CAMAT PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk. CABANG MEDAN SISINGAMANGARAJA - Muhayminah Muhayminah; Tan Kamello; Utary Maharany Barus; Rosnidar Sembiring (Universitas Sumatera Utara, 2017)
ABSTRACT Giving credit to the land security Certificate (SK) Head carried out by PT. Bank Rakyat Indonesia (Persero) Tbk. Medan SM. Raja to facilitate the debtor in obtaining loans for micro-enterprises, but SK Head can not be done Encumbrance because not registered in the State Land Board that need to disertipikatkan. Based on the above background that problems found first legal power of SK Head over land ownership, two credit granting process with guaranteed SK Head at PT. Bank Rakyat Indonesia (Persero) Tbk. Medan SM. Raja, and three legal protection against creditors in their lending with collateral land use Letter Head. Keywords : Bank , Credit, Guarantee, Letter Heads